2012
DOI: 10.1007/s10750-012-1139-4
|View full text |Cite
|
Sign up to set email alerts
|

Fish diversity and assemblage patterns along the longitudinal gradient of a tropical river in the Indo-Burma hotspot region (Ping-Wang River Basin, Thailand)

Abstract: The relationships between environmental variables as descriptors to the fish community, in terms of species diversity indices, and the fish assemblage patterns along the longitudinal gradient in a rhitral environment of a large river system located in the Indo-Burma hot spot (Ping-Wang River Basin) were studied. Fish data and water quality parameters were collected between January 1996 and April 2009. The three most diverse families were Cyprinidae, Balitoridae, and Cobitidae, respectively. Three physicochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 51 publications
1
12
0
1
Order By: Relevance
“…Along the upstream-downstream gradient, various environmental factors gradually vary downstream, such as energy production and consume (Vannote, Minshall, Cummins, Sedell, & Cushing, 1980), habitat volume and diversity (Schlosser, 1982), environmental stability (Taylor & Warren, 2001) and so on. The longitudinal patterns of how fish assemblages vary along this gradient have been substantially surveyed till now (e.g., Mazzoni & Lobón-Cerviá, 2000;Oberdorff, Guilbert, & Lucchetta, 1993;Suvarnaraksha, Lek, Lek-Ang, & Jutagate, 2012;Torgersen, Baxter, Li, & Mcintosh, 2006). Many researchers have found that local species richness of stream fishes increase downstream, obtain the maximum at the middle reaches and decrease at the lower reaches of streams (e.g., Minshall et al, 1985;Oberdorff et al, 1993;Sui, Lu, Yan, Chen, & Jia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Along the upstream-downstream gradient, various environmental factors gradually vary downstream, such as energy production and consume (Vannote, Minshall, Cummins, Sedell, & Cushing, 1980), habitat volume and diversity (Schlosser, 1982), environmental stability (Taylor & Warren, 2001) and so on. The longitudinal patterns of how fish assemblages vary along this gradient have been substantially surveyed till now (e.g., Mazzoni & Lobón-Cerviá, 2000;Oberdorff, Guilbert, & Lucchetta, 1993;Suvarnaraksha, Lek, Lek-Ang, & Jutagate, 2012;Torgersen, Baxter, Li, & Mcintosh, 2006). Many researchers have found that local species richness of stream fishes increase downstream, obtain the maximum at the middle reaches and decrease at the lower reaches of streams (e.g., Minshall et al, 1985;Oberdorff et al, 1993;Sui, Lu, Yan, Chen, & Jia, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A coherent approach to understanding these mechanisms is to compare communities along rivers, since fluvial and geomorphological differences occur longitudinally (Angermeier and Karr 1983, Ibañez et al 2007, Silva et al 2013. In this sense, the composition and diversity of the aquatic fauna have showed longitudinal changes, with adjustments at each local environmental conditions to its functioning along river system networks (Vannote et al 1980, Oberdorff et al 1993, Ferreira and Petrere Jr 2009, Suvarnaraksha et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fish community structures converge to similar patterns along biogeographically distinct rivers, regardless of their phylogenetic and historical constrains (Ibañez et al 2009). In this sense, geomorphological parameters, such as altitude, discharge, water velocity and channel depth, have more influence in predicting the increases in local fish richness/diversity and changes in fish community composition along the headwater-mouth direction, than physicochemical water variables (Lorion et al 2011, Suvarnaraksha et al 2012. For example, headwater reaches with fast water and low environmental heterogeneity has shown few species that are able to survive under such conditions, while larger and more diversified downstream habitat reaches tend to support a richer and more diverse ichthyofauna (Ibañez et al 2007, Suvarnaraksha et al 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suvarnaraksha et al (2012) demonstrated that the assemblage patterns along the longitudinal gradient of rivers in Thailand can be classified according to their habitat preferences:…”
mentioning
confidence: 99%